Peran Istri Sebagai Perempuan Karier Dalam Memenuhi Hak Dan Kewajibannya Guna Mewujudkan Keluarga Sakinah Di Desa Sukolilo Kecamatan Wajak Kabupaten Malang - Mufti Kamal (Jurnal Riset Multidisiplin Edukasi, 2024)
The increasing number of wives who pursue professional careers has become an interesting social phenomenon to study, particularly within the context of Muslim families. In Islam, women hold an honorable position and are permitted to work as long as they adhere to religious norms and do not neglect their household responsibilities. This study aims to analyze the role of wives as career women in fulfilling their rights and obligations to realize a sakinah (harmonious and peaceful) family in Sukolilo Village, Wajak District, Malang Regency. This research employs a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation, and analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The results show that wives who work in Sukolilo Village are generally able to balance their dual roles between career and domestic responsibilities. The main factors encouraging them to work include economic necessity, social interaction, and self-actualization. Their careers contribute positively to family welfare, mutual respect between spouses, and serve as a role model for their children. However, some negative impacts such as physical exhaustion and reduced family time may occur if time management and communication are not well maintained. Efforts to achieve a sakinah family are carried out through fair division of roles, open communication, disciplined time management, and the strengthening of spiritual values within the household.